Assessment of shoppers knowledge and perception towards plastic bag campaign in Kuala Lumpur - Syed Ismail, Sharifah Norkhadijah; Suhaimi, Nur Syakirah Hanani; Karuppiah, Karmegam (Human Resource Management Academic Research Society, 2021)
The study measures the shopper's knowledge and perception about the plastic bag campaign among the urban population. A survey was conducted among 198 shoppers from three different retailers (i.e. hypermarket, supermarket, and convenience store) in Kuala Lumpur. Respondents' knowledge and perception were assessed through a questionnaire. Results show a high number of shoppers (72.7%) participated in the plastic bag campaign. The remaining 27.3% who not participating were given a reason of inconvenient to carry other bags during shopping activity (18.7%) and a plastic bag was lighter and easy to carry (18.2%). The majority of the shoppers (53%) have a moderate level of knowledge about the plastic bag campaign. As for perception, the majority of the shoppers (78.3%, N = 155) have a very good perception of the campaign. The majority (40.9%) of the shoppers agree that the campaign was at the right time and they have highly supported the campaign (53.0%). The chi-Square analysis determined a significant association between the level of shoppers' knowledge with education (X2 = 15.902, p = 0.003). Meanwhile, for the perception, significant associations were determined between gender (X²=11.078, p=0.004), occupations (X²=18.583, p=0.046), marital status (X²=11.712, p=0.003), and age group of shoppers (X²=17.602, p=0.007). In conclusion, the shopper's participation, knowledge, and perception towards the plastic bag campaign in this study can be considered at a good level.